Spiritual Level Relationship with Resilience in Diabetes Mellitus Patients - Danu Mangippu Pasaribu; Yesi Hasneli; Hellena Deli (CV. Rayyan Dwi Bharata, 2023)
Introduction: Patients with Diabetes Mellitus (DM) often experience psychological problems that affect the daily management of DM. Spirituality provides the ability to do positive coping so that someone becomes resilient. Purpose: This study aims to determine the relationship between spiritual level and resilience in Diabetes Mellitus patients. Methods: Quantitative research design and cross sectional approach. The research sample was 100 respondents selected based on inclusion criteria using a purposive sampling technique. Measuring tools used are DSES and CD-RISC-25 questionnaires. The analysis used was univariate and bivariate analysis using the Chi-Square test with an Î± value of 0.05. Results: Statistical test using the Chi-Square test obtained p-value (0.004) Î± (0.05). Conclusion: There is a relationship between spiritual level and resilience in Diabetes Mellitus patients (p-value 0.004). DM sufferers are expected to be able to develop their adaptive abilities to overcome their illness by having a good spiritual approach to God as the main source of strength, building good intrapersonal and interpersonal relationships as the main coping in overcoming negative feelings due to their illness.